2008
DOI: 10.1590/s0004-27302008000800030
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosis for CYP21A2 mutation considered as 21-hydroxylase deficiency in neonatal screening

Abstract: Steroid 21-hydroxylase defi ciency (21-OHD) accounts for more than 90% of congenital adrenal hyperplasia. CAH newborn screening, in general, is based on 17-hydroxyprogesterone dosage (17-OHP), however it is complicated by the fact that healthy preterm infants have high levels of 17-OHP resulting in false positive cases. We report on molecular features of a boy born pre-term (GA = 30 weeks; weight = 1,390 g) with elevated levels of 17-OHP (91.2 nmol/L, normal < 40) upon neonatal screening who was treated as hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The more interesting finding of our study is submission the percent of variants in CYP21A2 gene, for instance: rs6477 (56%), rs6468 (8%), rs6474 (12%), rs6472 (16%), rs6473 (16%), rs6446 (16%) andrs193922546, rs530758070, rs11970671, rs61732108, rs778403992, rs1058152 and rs562025438 each (4%). The current study is the first report which gives distribution of the variants in Iranian population; however it was reported in other countries of the world (31,32). Additionally, our study indicated correlation between some of these variants, which is shown in Table 4.…”
Section: Discussionsupporting
confidence: 51%
“…The more interesting finding of our study is submission the percent of variants in CYP21A2 gene, for instance: rs6477 (56%), rs6468 (8%), rs6474 (12%), rs6472 (16%), rs6473 (16%), rs6446 (16%) andrs193922546, rs530758070, rs11970671, rs61732108, rs778403992, rs1058152 and rs562025438 each (4%). The current study is the first report which gives distribution of the variants in Iranian population; however it was reported in other countries of the world (31,32). Additionally, our study indicated correlation between some of these variants, which is shown in Table 4.…”
Section: Discussionsupporting
confidence: 51%